Parietal-specific activation reveals pain from inadequate levels of altitude acclimatization/ adaptation - Shurong Jia; Niannian Wang; Rui Su; Hailin Ma; Hao Li (PLoS ONE, 2025)
Objective Pain is acknowledged as a prominent physiological symptom of high-altitude (HA) acclimatization, yet there exists a dearth of empirical support regarding the impact of variations in HA acclimatization/ adaptation on pain perception in hypoxic environments. Methods A total of 65 HA residents were recruited, all of whom had resided continuously in HA regions for a minimum duration of one month. The study involved an assessment of peripheral oxygen saturation (SpO2) and haematocrit (HCT) levels, administration of the Pain Frequency, Intensity and Burden Scale (P-FIBS), and the resting-state electroencephalogram (rs-EEG) signals of all frequency bands including delta, theta, alpha, beta and gamma were acquired from the frontal lobe, parietal lobe, temporal lobe and occipital lobe. Residents’ acclimatization levels were assessed using altitude acclimatization/ adaptation index (AAI), and categorized into high and low AAI groups. Results Residents in the high-AAI group reported lower levels of perceived pain compared to those in the low-AAI group (t = 1.61, p = 0.04). Further analysis using EEG frequency bands demonstrated that parietal delta (β = −0.35, 95%CI = [−1.18, −0.01]) and beta (β = 0.31, 95%CI =[0.01, 1.19]) powers acted as mediators in the relationship between AAI and pain perception. Brain waves of other frequencies, including theta (β = −0.02, 95%CI = [−0.46, 0.41]), alpha (β = −0.03, 95%CI = [−0.34, 0.18]), and gamma (β = −0.06, 95%CI =[−0.09, 0.03]), did not show a significant mediating effect. Conclusions A lower level of HA adaptation indicates a higher intensity of pain perception. The enhancement of EEG activity might be regarded as a compensatory mechanism. It endeavors to maintain the normal operation of the body’s physiological functions by increasing the efficiency of neural activities, thereby helping individuals to improve their adaptability to the HA environment. The parietal lobe, as a key brain region responsible for processing sensory information throughout the body, exhibits the most significant activation state compared with other brain regions when an individual is in a HA environment and the adaptation level shows dynamic changes. Notably, once the beta waves, which are highly associated with attention, are activated, the increase in an individual’s alertness often indicates that the individual will experience a more intense and higher level of pain sensation. However, the activation of delta waves, which usually occur during the stage of deep sleep and can prompt the brain to maintain a relaxed state, generally means that the individual will perceive a relatively lower level of pain. Consequently, the rs-EEG power in the delta and beta frequency bands of the parietal lobe region serves as an important mediating factor in the connection between AAI and pain perception.